Simulation of fault analysis and determination of circuit breaker rating / Mohammad Idham Mahdi @ Mahadi - Mahdi @ Mahadi, Mohammad Idham (2012)
This paper studies the analysis of fault and how to determine circuit breaker rating using PSS-Adept. Short circuits are the most frequent type of faults that occur in high voltage networks. When a fault occurs, a short-circuit current flows through the line and equipment's, it may cause considerable damage to equipment's and interruption of service to the consumers. Damage from short circuits can be prevented by employing fuses, circuit breakers, or other overload protection, which discontinue the electrical flow/ This paper analyzes faults on IEEE-recommended 6-Bus and 9-Bus system using power system simulation programmed for planning, design and analysis of distributed system (PSS/Adepts). However in this simulation software, the overcurrent (OC) relays will represent the protective device, the circuit breakers rating will be determined after. The coordination of OC relays will also be determined.